TEKNIK MENERAPKAN BACKING TRACK DALAM MUSIK IBADAH GEREJA - Yosef Anang; Christanto Hadijaya; Yunatan Krisno Utomo (JOURNAL of THEOLOGICAL STUDENTS, 2021)
With the development of global technology, music technology has also developed, including music technology in the church. Many churches are taking advantage of the development of sound technology to provide a platform for new generations to worship without abandoning the needs of the previous generation, Backing track technology that runs and blends with their worship music, helping to build an atmosphere of praise and worship. This study uses a qualitative research method with a participant observation approach, where the researcher combines document analysis, interviewing respondents and informants, direct observation and participation (involvement) and introspection. The results obtained are the meaning of the existence of the Backing track in the music accompaniment of worship. The conclusion obtained is that Backing track makes music accompaniment to worship beyond the imagination of musicians as well as being a "partner" in music for Abbalove Taman Palem. The elements of technology used to implement the Backing track were adjusted to keep it running in tandem with the elements of the original worship music, namely the combo band. The existence of the Backing track is not the core in building an atmosphere of praise and worship, but the Backing track is only a tool in conveying the message of the song, and strengthening the psychological element of the song that is sung.